Metformin and carotid intima‐media thickness in never‐smokers with type 1 diabetes: The REMOVAL trial. Issue 6 (8th March 2021) - Timmons, Joseph G.; Greenlaw, Nicola; Boyle, James G.; Chaturvedi, Nish; Ford, Ian; Brouwers, Martijn C. G. J.; Tillin, Therese; Hramiak, Irene; Hughes, Alun D.; Jenkins, Alicia J.; Klein, Barbara E. K.; Klein, Ron; et al.
Abstract: Aim: To determine whether metformin's effects on carotid artery intima‐media thickness (cIMT) in type 1 diabetes differ according to smoking status. Methods: Regression model effect estimates for the effect of metformin versus placebo (double‐blind) on carotid IMT were calculated as a subgroup analysis of the REMOVAL trial. Results: In 428 randomized participants (227 never‐smokers, 201 ever‐smokers), averaged mean carotid IMT progression (per year) was reduced by metformin versus placebo in never‐smokers (−0.012 mm, 95% CI −0.021 to −0.002; p = .0137) but not in ever‐smokers (0.003 mm, 95% CI −0.008 to 0.014; p = .5767); and similarly in non‐current smokers (−0.008 mm, 95% CI −0.015 to −0.00001; p = .0497) but not in current smokers (0.013 mm, 95% CI −0.007 to 0.032; p = .1887). Three‐way interaction terms (treatment*time*smoking status) were significant for never versus ever smoking ( p = .0373, prespecified) and non‐current versus current smoking ( p = .0496, exploratory). Averaged maximal carotid IMT progression (per year) was reduced by metformin versus placebo in never‐smokers (−0.020 mm, 95% CI −0.034 to −0.006; p = .0067) but not in ever‐smokers (−0.006 mm, 95% CI −0.020 to 0.008; p = .4067), although this analysis was not supported by a significant three‐way interaction term. Conclusions: This subgroup analysis of the REMOVAL trial provides additional support for a potentially wider role of adjunct metformin therapy in cardiovascular risk management in type 1 diabetes, particularly for individuals who have never smoked cigarettes.